2013
DOI: 10.1186/1756-8722-6-37
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA: a new player in cancer

Abstract: Emerging evidence showed that long non-coding RNAs (lncRNAs) play important roles in a wide range of biological processes and dysregulated lncRNAs are involved in many complex human diseases, including cancer. Although a few lncRNAs’ functions in cancer have been characterized, the detailed regulatory mechanisms of majority of lncRNAs in cancer initiation and progression remain largely unknown. In this review, we summarized recent progress on the mechanisms and functions of lncRNAs in cancer, especially focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
319
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(323 citation statements)
references
References 76 publications
(82 reference statements)
1
319
0
3
Order By: Relevance
“…lncRNAs have been implicated in a large number of cellular processes, such as proliferation, cell cycle progression, growth, and apoptosis (Mercer et al, 2009). In the last 10 years, an increasing number of studies have reported that lncRNA expression is obviously dysregulated in various cancers and that these lncRNAs play critical roles in tumor development, progression, and metastasis (Gibb et al, 2011;Zhang et al, 2013a). In human osteosarcoma, Sun et al (2015b) demonstrated that the lncRNA HULC was significantly upregulated in osteosarcoma tissues and that the overexpression of HULC was correlated with advanced clinical stage and distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…lncRNAs have been implicated in a large number of cellular processes, such as proliferation, cell cycle progression, growth, and apoptosis (Mercer et al, 2009). In the last 10 years, an increasing number of studies have reported that lncRNA expression is obviously dysregulated in various cancers and that these lncRNAs play critical roles in tumor development, progression, and metastasis (Gibb et al, 2011;Zhang et al, 2013a). In human osteosarcoma, Sun et al (2015b) demonstrated that the lncRNA HULC was significantly upregulated in osteosarcoma tissues and that the overexpression of HULC was correlated with advanced clinical stage and distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years, lncRNAs have been found to be associated with wide range of biological regulatory functions (31). Many studies have reported that lncRNAs participated in pathogenesis of cancers, epigenome, levels of transcription and post-transcription (32)(33)(34). To date, only a few studies have reported the expression profiles of lncRNA in GC by microarray or sequencing, and with small sample size (35).…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies suggest that lncRNAs derived from multiple tumors are overexpressed or underexpressed, influencing cancer growth, survival and migration or invasion (26)(27)(28). Furthermore, lncRNAs have been shown to be dysregulated in various types of cancer and several lncRNAs have been functionally associated with cancer cell differentiation (14,29,30).…”
Section: Discussionmentioning
confidence: 99%